Science and knowledge are a manifestation of the Arab-Islamic civilization - Salman, Mohammed (Journal of College of Education, 2022)
ABSTRACT The research talks about the role of science and knowledge in Islamic civilization, and shows the great position that science and knowledge have enjoyed in the Noble Qur’an and the honorable Sunnah of the Prophet, until science and knowledge have become one of the faces and manifestations of Arab Islamic civilization. The research consisted of an introduction and three sections, and concluded with a list of sources and references. The topic dealt with the interpretation of the Arab civilization and the prosperity it reached, then it shows definitions and clarification of science and knowledge. Then the list of sources.